Modified Moringa oleifera Seed Husk Biomass as an Eco-Friendly Adsorbent for Emerging Contaminant Bisphenol A Removal from Water - Cely Roledo; Victória Agnes Salgueiro Ferreira; Kleper de Oliveira Rocha; Adriano Gonçalves dos Reis (Materials Research, 2025)
Bisphenol A (BPA), commonly found in plastics and epoxy resins, poses serious risks to human and animal health, particularly affecting reproduction and hormonal balance. This study investigates the removal of BPA from water using modified Moringa oleifera seed husks (H-MOH300) as a sustainable adsorbent. The husks were chemically activated with phosphoric acid and thermally treated at 300°C, yielding a BET surface area of 380 m2 g−1 and a pore volume of 0.282 cm3 g−1. SEM analysis showed a porous and fibrous morphology, while XRD indicated a crystalline nature. FTIR identified hydroxyl, aromatic, and carboxylic functional groups. The process followed the Langmuir isotherm model, achieving a maximum adsorption capacity of 27.5 mg g−1 at 22°C. Thermodynamic analysis indicated a spontaneous, endothermic process driven by electrostatic and π-π interactions. Regeneration tests up to 5 cycles confirmed H-MOH300’s reusability, demonstrating its potential as a cost-effective, eco-friendly solution for BPA removal.